Efficacy of Single Intra-Articular Injection of Platelets Rich Plasma in Patients with Early Osteoarthritis of Knee Joint (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To evaluate the role and effectiveness of intra-articular platelet rich plasma (PRP) injection for pain management among patients having early osteoarthritis of knee joint. Methods: All the patients presenting between February 15, 2015 to August 15, 2015 with early osteoarthritis of knee with a pain score of 8 to 10 on visual analogue scale (VAS) were included in the study. All patients were given single intra-articular platelet rich plasma injection. All patients were followed for 12 weeks. The outcome was measured in terms of mean reduction in VAS pain score from the base line. Results: There were 93 patients with mean age of 49.17 Â± 7.993 ranged from 33 to 60 years of age were selected. Thirty eight patients (40.9%) were male, whereas 55 patients (59.1%) were female. Mean reduction in VAS Score was 3.31 Â± 1.260 ranged from 1 to 6. Gender, age or duration of disease shown no statistical difference in outcome illustrated. Conclusion: Present study reveals that patients having early osteoarthritis of knee joints after injecting intra-Articular platelet rich plasma injection are efficacious in reducing 50.0% of pain measured of VAS score.Key Words: Osteoarthritis, Intra-Articular, Platelet Rich Plasma Injection (PRP), Visual analog score (VAS) INTRODUCTION Degenerative